Implementation of Physics Learning by Using the Guided Inquiry Method on the subject matter of Ohm's Law and Series-parallel Circuits, Effectiveness in terms of Learning Outcomes, Involvement and Constraints - Maria Goretti Molla (International Journal of Basic and Applied Science, 2022)
This study aims to determine: (1) the effectiveness of the learning of physics using guided inquiry methods in terms of improving student learning outcomes, (2) Does the implementation of learning physics using guided inquiry on the subject of ohms law, series and parallel circuits can be involve students, (3) what obstacles or difficulties experienced by students in the implementation of learning physics using guided inquiry on the subject of ohms law, series and parallel circuits and how it can help students to overcome obstacles or difficulties faced by students in learning. The research was carried on in high school Karanu Waikabubak Sumba Barat-NTT on 29 April 2011 until 11 May 2011. Object of research are 15 students in select classes Xd researchers based on the results of a pretest that was done of students as treament or treatment that is given researcher. Data collection include: pretest, postest, learning activities with guided inquiry method using worksheets, student involvement Sheet observations, and interviews. The results showed that the learning of physics using guided inquiry on the subject of ohms law, series and parallel circuits: (1) The effectiveness of learning physics using guided inquiry methods in terms of student learning outcomes by using a test analysis of dependent T-test level α = 0.05 (2) lack of involving students in all learning activities using the methods of guided inquiry, (3) know the obstacles or difficulties the student and knowing how to cope with natural constraints on students.